Legal Protection Efforts for Wives and Children in Divorces Caused by Husband's Nusyuz Case - Nabila Rahmawati Rama; R Rizka (Universitas Muhammadiyah Surakarta, 2023)
Divorce is the main cause of the dissolution of a marriage, as stated in Article 38 of UUP No.1 of 1974. Currently, one of the problems in society is the nusyuz case, which is defined as disobedience or non-compliance between husband and wife in prioritizing roles and obligations. contained in a marriage bond. The word nusyuz is found in Qs. An – Nisa verses 34 and 128, nusyuz cases are rife in religious courts. Therefore, the researcher used a normative juridical approach method by referring to Islamic law and positive civil law, statutory regulations and supported by secondary data in the form of interviews from several opinions and considerations of court judges' decisions. Comparisons with previous research can be found in interviews conducted by researchers with one of the chairmen of PA Surakarta, in terms of considering a decision in the form of livelihood, as well as developments in regulations issued by the Supreme Court. Often the children and wife are still the parties who suffer losses after a divorce, the basis for the judge's consideration in granting maintenance rights to the wife and children after the divorce. It is explained in Islamic law using 4 (four) methods: